Extracapsular cataract extraction training: junior ophthalmology residents' self-reported satisfaction level with their proficiency and initial learning barrier. Issue 1077 (9th June 2015) - Ting, Daniel Shu Wei; Tan, Sarah; Lee, Shu Yen; Rosman, Mohamad; Aw, Ai Tee; Yeo, Ian Yew San
ABSTRACT: Purpose: To investigate residents' self-reported satisfaction level with their proficiency in extracapsular cataract extraction (ECCE) surgery and the initial barriers to learning the procedure. Methods: This is a single-centre prospective descriptive case series involving eight first-year ophthalmology residents in Singapore National Eye Center. We recorded the demographics, frequency of review by the residents of their own surgical videos and their satisfaction level with their proficiency at each of the ECCE steps using a 5-point Likert scale. All ECCE surgical videos between October 2013 and May 2014 were collected and analysed for the overall time taken for the surgery and the time taken to perform the individual steps of the procedure. Results: The mean age of the residents was 27.6±1.5 years and 62.5% (5/8) were women. More than half (62.5%, 5/8) reviewed their own surgical videos while 37.5% (3/8) discussed the surgical videos with their peers or supervisors. Of the ECCE steps, the residents were most dissatisfied with their proficiency in performing irrigation and aspiration (87.5%, 7/8), followed by suturing (62.5%, 5/8), intraocular lens insertion (62.5%, 5/8) and tin can capsulotomy (62.5%, 5/8). The average time taken for each ECCE case was 55.0±12.2 min and, of all the steps, most time was spent on suturing (20.5±6.8 min), followed by irrigation and aspiration (5.5±3.6 min) and tin can capsulotomy (3.3±1.8 min). Conclusions: The first-year ophthalmology residents were most dissatisfied with their proficiency in irrigation/aspiration, suturing and tin can capsulotomy. More training needs to be directed to these areas during teaching sessions in the operating room, wet laboratory or cataract simulation training sessions.